1997
DOI: 10.1073/pnas.94.19.10391
|View full text |Cite
|
Sign up to set email alerts
|

The type 2 iodothyronine deiodinase is expressed primarily in glial cells in the neonatal rat brain

Abstract: Thyroid hormone plays an essential role in mammalian brain maturation and function, in large part by regulating the expression of specific neuronal genes. In this tissue, the type 2 deiodinase (D2) appears to be essential for providing adequate levels of the active thyroid hormone 3,5,3-triiodothyronine (T3) during the developmental period. We have studied the regional and cellular localization of D2 mRNA in the brain of 15-day-old neonatal rats. D2 is expressed in the cerebral cortex, olfactory bulb, hippocam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
197
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 336 publications
(210 citation statements)
references
References 45 publications
13
197
0
Order By: Relevance
“…Studies in animal models have revealed that approximately up to 80 % of the active thyroid hormone T3 is produced locally in the CNS (Crantz et al, 1982) suggesting a prominent role of the activating enzyme D2 which exclusively catalyses outer ring deiodination. In contrast to thyroid hormone receptors that are highly enriched in oligodendrocytes and neurons, D2 is predominantly found in astrocytes throughout the brain (Guadano-Ferraz et al, 1997). In the rat, D2 expression is first detectable at E16.5 and increases successively until postnatal day 15.…”
Section: Metabolism Of Thyroid Hormones By Brain Deiodinasesmentioning
confidence: 98%
“…Studies in animal models have revealed that approximately up to 80 % of the active thyroid hormone T3 is produced locally in the CNS (Crantz et al, 1982) suggesting a prominent role of the activating enzyme D2 which exclusively catalyses outer ring deiodination. In contrast to thyroid hormone receptors that are highly enriched in oligodendrocytes and neurons, D2 is predominantly found in astrocytes throughout the brain (Guadano-Ferraz et al, 1997). In the rat, D2 expression is first detectable at E16.5 and increases successively until postnatal day 15.…”
Section: Metabolism Of Thyroid Hormones By Brain Deiodinasesmentioning
confidence: 98%
“…The concentration of the active hormone T3 in CNS is controlled by two local mechanisms: the uptake of circulating plasma T4 and T3 mediated by transporters located in the blood-brain barrier and the plasma membrane of neural cells, such as MCT8 or OATP1C1 (33) or local production of T3 through the D2-mediated deiodination of T4. The local activation of T4 at a tissue level is more important in providing T3 to the neurons than is plasma (17,34,35). A gene expression study recently conducted in mice with no D2 or MCT8 (double KO mice), showed that MCT8 has little effect on the expression of multiple genes regulated by the thyroid hormone due to a compensatory increase in D2 activity in discrete areas of mouse cerebrum.…”
Section: Deiodinases and Developmentmentioning
confidence: 99%
“…In contrast, in D3KO mice, despite normal or low serum thyroid hormone concentrations, the absence of D3 activity in the brain results in excessive T3 effects in multiple brain regions, causing altered neuronal function (37). A paracrine paradigm for T3 supply is thought to occur in the central nervous system: D2 is highly expressed in glial cells providing T3 for neurons, which have higher D3 than D2 activity (34). This paracrine response is present in vivo as well, since the systemic administration of LPS, which induces a rapid increase of D2 in the tanycytes of the mediobasal hypothalamus and a consequent suppression of TRH expression (38), is absent in D2KO mice (39).…”
Section: Deiodinases and Developmentmentioning
confidence: 99%
“…Their results were in agreement with previously reported data on the mRNA distribution of rat D2. Guadaño-Ferraz et al (1997) reported in situ hybridization studies for D2 in neonatal rat brain. They found excessive D2 mRNA expression in different brain areas, but more importantly, mainly, if not exclusively, in glial cells.…”
Section: Introductionmentioning
confidence: 99%